Effect Of Different Sugars On Shoot Regeneration Of Maize (Zea Mays L.) - Gauchan, DP (Kathmandu University Journal of Science, Engineering and Technology, 2012)
Effect of various concentrations of different sugars was investigated for induction of root and shoot from maize. The seedling development was induced with the application of fructose, maltose and sucrose at different concentrations (0.25%, 0.5%, 0.75%, 1.0%, 2.5%, 5%, and 10%) of each. Dissected embryos were transferred in ½ MS basal media fortified with various concentrations of different carbon sources. In vitro regenerated maize plantlets were healthy and attained a length of 12.2 cm at 1.0 % concentration in maltose within a week. Out of three sugars low concentration (0.25%- 2.5%) of maltose and sucrose exhibited the maximum shoot and root growth. All the concentrations of maltose and sucrose showed the good growth response of shoot and root. DOI: http://dx.doi.org/10.3126/kuset.v8i1.6051 KUSET 2012; 8(1): 119-124